Evolution of a pentameral body plan was not linked to translocation of anterior Hox genes: the echinoderm HOX cluster revisited. Issue 2 (13th January 2016) - Byrne, Maria; Martinez, Pedro; Morris, Valerie
SUMMARY: Echinodermata is a large phylum of marine invertebrates characterized by an adult, pentameral body plan. This morphology is clearly derived as all members of Deuterostomia (the superphylum to which they belong) have a bilateral body plan. The origin of the pentameral plan has been the subject of intense debate. It is clear that the ancestor of Echinodermata had a bilateral plan but how this ancestor transformed its body "architecture" in such a drastic manner is not clear. Data from the fossil record and ontogeny are sparse and, so far, not very informative. The sequencing of the sea urchin genome a decade ago opened the possibility that the pentameral body plan was a consequence of a broken Hox cluster and a series of papers dwelt on the putative relationship between Hox gene arrangements in the chromosomes and the origin of pentamery. This relationship, sound as it was, is challenged by the revelation that the sea star HOX cluster is, in fact, intact, thus falsifying the hypothesis of a direct relationship between HOX cluster arrangement and the origin of the pentameral body plan. Here, we explore the relationship between Hox gene arrangements and echinoderm body "architecture, " the expression of Hox genes in development and alternative scenarios for the origin of pentamery, with putative roles for signaling centers in generating multiple axes.